MAKNA SIMBOLIK SERAH-SERAHAN DALAM UPACARA PERKAWINAN ADAT JAWA DI DESA TANJUNG BELIT KECAMATAN SIAK KECIL KABUPATEN BENGKALIS PROVINSI RIAU - Windyarti, Retno; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Serah-serahan is one of the ceremony or procession contained in customary marriages Java in Desa Tanjung Belit Kecamatan Siak Kecil Kabupaten Bengkalis Province Riau. In the Serah-serahan are aspects that will be symbolic meanings that are represented on the various physical objects or items used. The purpose of this research was to determine the meaning of the symbolic transfer of deliverables in terms of physical and social objects and values contained in traditional Javanese wedding ceremony.This research receipts qualitative method with symbolic interaction approach. The subject of research in the form of 5 people who are public figures, interpreter manten, the parties conducting the Srah-serahan and villagers of Desa Tanjung Belit Kecamatan Siak Kecil Kabupaten Bengkalis Province Riau selected use technique of purposive. Data obtained through in-depth interview and documentation. This research use technique analyse data of interactive by using data collecting technique, data reduction, presentation of data and withdrawal of conclusion.The result of research showed that symbolic situation of Serah-serahan in traditional Javanese wedding ceremony Desa Tanjung Belit Kecamatan Siak Kecil Kabupaten Bengkalis Province Riau include physical objects such as pisang sanggan, suruh ayu, cincin, seperangkat busana putri, traditional meal, and some money and the social objects from the Serah-serahan in traditional Javanese wedding ceremony include all the procession of Javanese wedding ceremony. In the Serah-serahan contained the social value and culture value.Keywords: Symbolic Meaning, Symbolic Interaction Theory, Serah-serahan